Pengaruh Kompensasi, Pengalaman Kerja, dan Budaya Organisasi terhadap Kinerja Pegawai Bapelitbang Kabupaten Bintan melalui Pengembangan Karir sebagai Variabel Intervening - Octavia, Resti; Rumengan, Angelina Eleonora; Satriawan, Bambang (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to determine the influence of compensation, work experience, and organizational culture on the performance of Bintan Regency Bapelitbang employees through career development as an intervening variable. The sampling technique in this research uses a saturated sampling technique where the entire population in this research is sampled, the total population is 78 people . Data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this research show that simultaneously and partially there is a positive and significant influence between the variables of compensation, work experience, organizational culture on career development. Partially, compensation, organizational culture and career development variables have a significant effect on performance variables, but work experience variables do not have a significant effect on performance. The influence of compensation, work experience and organizational culture have a significant effect on performance through career development for Bintan Regency Bapelitbang employees.